Zarządzenie o zgodzie na widzenie z osobą tymczasowo aresztowaną - Kalisz, Tomasz (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
A particularly severe restriction of the right of individuals held on remand comes with the normative regulations concerning visit entitlements. As a rule, in the Polish legal order an individual held on remand may be allowed a visit after the authority under whose charge he or she is detained has issued a visiting order. A refusal to issue a visiting order for an individual held on remand to see a close relative is a decision taken in the course of enforcement proceedings for which there is a separate appeal procedure, different from the basic form of control. Special grounds are also provided for such a refusal.
Keywords: tymczasowe aresztowanie; porządek odwiedzin; wykonywanie orzeczeń; prawo karne